Oxygen self-doped carbon aerogels: A solid-phase microextraction fiber coating for the extraction and detection of trace phthalate esters. Issue 15 (13th October 2022) - Dong, Zong-Mu; Sun, Tong; Zhang, Peiyi; Xia, Qian; Zhao, Guang-Chao
ABSTRACT: In this study, an oxygen self-doped carbon aerogel (ODCA), synthesized via ambient pressure drying and carbonization, was employed as solid-phase microextraction (SPME) coating material for phthalate esters (PAEs) detection in water samples by gas chromatography (GC) coupled with a flame ionization detector (FID). The materials were obtained by incomplete carbonization of the phenolic aerogel at a controlled temperature of 950°C, which leads to a certain amount of oxygen self-doping in the carbon aerogel. The ODCA-coated fiber exhibited fascinating extraction properties for PAEs mainly due to its oxygen active sites, π-π interaction, high surface area, and porosity of carbon aerogel. This as-proposed fiber showed wide linearity ranges (0.5–500, 1.0–500, 1.0–1000, 2.0–500 μg L −1, respectively), and provided low limits of detection (LOD, 0.17–0.83 μg L −1 ) for PAEs analysis under the optimal conditions. The single fiber and fiber-to-fiber relative standard deviations at 100 μg L −1 were observed in the range of 5.31%–10.37% and 9.17%–16.65%, respectively. Moreover, this method was also used for the determination of five PAEs in real water samples.